Unraveling Patterns of PETI in Sintang: The Urgency of Restorative Approach in Environmental Law Enforcement - Aura Putri Atmaja; Tri Atika Febriany; M Fajrin (DE LEGA LATA: JURNAL ILMU HUKUM, 2026)
Unlicensed Gold Mining (PETI) in Sintang Regency continues to be a complex multidimensional problem, not only affecting environmental damage, but also posing public health risks and exacerbating local socio-economic conditions. The criminalization of PETI perpetrators that has been pursued so far has proven ineffective in preventing illegal activities and restoring the damage that has occurred. This research criticizes the repressive approach through criminalization of PETI perpetrators and analyzes the urgency of applying a restorative justice approach as an alternative to sustainability-based legal settlements. Through empirical studies and in-depth interviews with officials and related agencies in Sintang, it is found that criminalization tends to ignore aspects of restorative justice for affected communities, and does not touch the structural and economic roots that drive PETI activities. Compared to the practice in Australia, which is more adaptive to the environmental approach, Indonesia is considered to have not integrated the principles of recovery in its law enforcement. Therefore, this research recommends a paradigm shift in environmental law from a punitive approach towards a restorative approach that emphasizes environmental restoration, community empowerment, and dialogical and sustainable conflict resolution.